Educommunication and Learning in the Digital Age: Transforming Virtual Education Environments - Salgado Aráuz, Georvany José; Hernández Bieliukas, Yosly Caridad (Scientific journal of social studies, 2025)
This paper explores the importance of communication in Virtual Learning Environments (VLE), where technologies, digital resources, and didactic methods are fundamental to facilitate learning. It highlights the relationship between human communication and education, underlining how virtual environments foster interaction and knowledge construction through interaction between participants, materials, and tutors. It focuses on audiovisual communication, which, by integrating images, text and audio, supports active and meaningful learning. Different approaches to online learning are presented, highlighting asynchronous and synchronous modalities, and how instructional design (such as the ADDIE model) enhances the effectiveness of communication in these environments. Communication is viewed as a complex, interdisciplinary process, and its relationship to the processes of understanding and learning, which are fundamental to knowledge construction, is explained. The concepts of interaction and interactivity in VLE are also examined, highlighting their importance in motivation and effective learning. Finally, Educommunication, which combines education and communication, is addressed, using digital technologies to create participatory and meaningful learning environments. The role of the online tutor is key to guide and support students, promoting effective communication and autonomous learning within these environments. The paper concludes with the importance of multimedia resources and interaction in VLEs, in addition to presenting the ADDIE model as an effective tool for instructional design and improving communication in virtual educational environments.